THE PRAGMATIC MEANINGS OF ADDRESS TERMS SAMPEYAN AND ANDA - Susanto, Djoko (Universitas Pendidikan Indonesia, 2014)
Abstract: This research investigates the use of sampeyan and anda by the students from Pasuruan and Probolinggo. Address terms is one of important tools in communication in Javanese society as it is used, for example, to designate the person they are talking to or to show the possession of formal and informal manners. However, the use of this address terms may have different interpretation across regions. This research is undertaken to find out (1) factors that influence the choice of address terms sampeyan and anda in Pasuruan and Probolinggo and (2) situations in which the interlocutors use the address terms sampeyan and anda. Several theories are used to help analyze the data, which include address terms (Wardhaugh, 2002), sampeyan and anda (Wolf Poedjosoedarmo, 1982), Politeness theory (Brown Levinson, 1987), and Power and Solidarity (Brown Gilman, 1960). The data were obtained from the results of observations, questionnaires and interviews with the participants. The results of the study show that both sampeyan and anda were found to be commonly used by the participants to address their lecturer, instead of using Bapak. This is, of course, uncommon from either the perspective of standard usage of Javanese or Indonesian language. This study also indicates that the participants used sampeyan to lecturer/teacher, kyai, parent, and older sibling because they wanted to express (1) express politeness and (2) to indicate informality. Concerning to the use of anda, this study reveals that the participants use this address term because of (1) more formal and appropriate manners in environmental education, (2) respecting person of higher social status and older person, (3) more polite and more appropriate than sampeyan, and (4) the use of Indonesian as a formal language. In some respect, however, the participants use anda to lecturer/teacher, which is not appropriate because they were not socially equal to the lecturer/teacher. Â This study provide important findings which reveal that the address term of sampeyan and anda, which are widely understood by Javanese to express respect, and to express distant relationship, might be perceived and used in different way by the students coming from Pasuruan and Probolinggo. Thus, it contributes to knowledge that using the address terms sampeyan and anda to persons of higher social status should not be any longer regarded as impolite utterances because it has become social norms in those specific communities.Â Keywords: Address terms, sampeyan, anda, kinship